2016
DOI: 10.1080/00918369.2016.1236590
|View full text |Cite
|
Sign up to set email alerts
|

“And Now I’m Just Different, but There’s Nothing Actually Wrong With Me”: Asexual Marginalization and Resistance

Abstract: This article explores the relationship between contemporary asexual lives and compulsory sexuality, or the privileging of sexuality and the marginalizing of nonsexuality. Drawing on 30 in-depth interviews, I identify four ways the asexually identified individuals in this study saw themselves as affected by compulsory sexuality: pathologization, isolation, unwanted sex and relationship conflict, and the denial of epistemic authority. I also identify five ways these asexually identified individuals disrupted com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 26 publications
1
41
0
Order By: Relevance
“…For example, Milks and Cerankowski (2014) argue asexuality has the potential to question a ‘mainstream culture, with its “make it sexy” imperative and “hot or not” hierarchy’ and to ‘radically rethink sexuality, queerness, desire, and intimacy in terms of not desiring sex, not having sex, or not experiencing sexual attraction’ (p. 314). Similar radical claims for asexuality include the problematising of ‘sex’ as an essential act (Flore, 2014; Pryzbolo, 2011), questioning a form of neoliberal ‘liberal humanism’ in which a productive (in all sense of the term) individual is valued (Gressgård, 2013; Pryzbolo, 2013), the ‘desexualisation’ of identity in favour of notions of difference (Gupta, 2017), and suggesting a ‘healthy’ lifestyle which does not require sex (Kim, 2010). A particularly confident version of this argument comes from Fahs (2010) who, in equating asexuality with a choice made by women, frames asexual people as ‘radical refusals’.…”
Section: The Politics Of Asexualitymentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Milks and Cerankowski (2014) argue asexuality has the potential to question a ‘mainstream culture, with its “make it sexy” imperative and “hot or not” hierarchy’ and to ‘radically rethink sexuality, queerness, desire, and intimacy in terms of not desiring sex, not having sex, or not experiencing sexual attraction’ (p. 314). Similar radical claims for asexuality include the problematising of ‘sex’ as an essential act (Flore, 2014; Pryzbolo, 2011), questioning a form of neoliberal ‘liberal humanism’ in which a productive (in all sense of the term) individual is valued (Gressgård, 2013; Pryzbolo, 2013), the ‘desexualisation’ of identity in favour of notions of difference (Gupta, 2017), and suggesting a ‘healthy’ lifestyle which does not require sex (Kim, 2010). A particularly confident version of this argument comes from Fahs (2010) who, in equating asexuality with a choice made by women, frames asexual people as ‘radical refusals’.…”
Section: The Politics Of Asexualitymentioning
confidence: 99%
“…First, whether asexuality is a potentially radical political formation is an empirical claim, which is not justified solely by rejecting a conservative human scientific approach. However, with the exception of Scherrer (2010) and Gupta (2017 see below), none of this literature has used empirical data. This is important for the second criticism: in making these arguments, asexuality is reified as a disembodied entity with its own agency: Asexuality, in choosing to repeat differently, must also choose to abandon its reactive, binary-bound sense of itself, focusing on what it does instead of what it does not do.…”
Section: The Politics Of Asexualitymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to a history of clinical approaches that have marginalized asexualities, popular assumptions about "human nature" have also pathologized asexuality. Sexual desire is often framed in the public imagination as an innate and universal experience among human beings (Gupta, 2017). As a result, research has shown that asexual individuals-or those who do not experience sexual desire-are viewed as "less human" (MacInnis & Hodson, 2012, p. 725).…”
Section: From Pathology To Identitymentioning
confidence: 99%